Current-voltage characteristics of diodes operating under explosive emission of electrons; Soviet Physics: Technical Physics; Vol. 18 - Bugaev S. P.; Zagulov E. A.; Litvinov E. A.; Mesyats G. A. Gennady Andreyevich (1973, 1973)
В фонде НТБ ТПУ отсутствует